The Impact of the Nam Et - Phou Louey National Park Conservation Project on the Economic Condition of the People in Hiem District, Houaphan Province - KHAMMESOUK, Khongthong; SIPHANTHONG, Bounthavy; SENGDARA, Chansamone; SIOUDOMPHAN, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Research on the impact of the Nam Et - Phou Louey National Park Conservation Project on the economic condition of the people in Hiem District, HuaPhan Province The aim of the research objectives is: 1) Checking the relationship between the independent variables in the effect model using the Pearson correlation coefficients method 2) The impact of the conservation project at the Nam Et - Phou Louey National Park Management Team on the economic condition of the people in Hiem District, HuaPhan Province. From the results of the analysis of the impact of the Nam Et - Phou Louey National Park Conservation Project on the economic condition of the people of Haim District, Huafan Province, it was found that, in checking the relationship between each independent variable, the Pearson correlation coefficients will be used to find the correlation coefficient of the independent variable by the method of Pearson. 99% and 95%, showing that the independent variables are related but not highly correlated or too high, the standard set by statistics to cause multi-collinearity. And from the results of the analysis of the impact of the Nam Et - Phou Louey National Park Conservation Project on the economic condition of the people of Hyem District, HuaPhan Province, in the 7 target villages, the variables include 2 major aspects, namely: occupational factors with 2 factors and land holding factors with 4 aspects as co-variables. The following variables were found: The factors that affect the effect of the Nam Et - Phou Louey National Park Conservation Project on the economic condition of households in the target villages of the project are more than the production variable (farmland, Hai land, garden land). Therefore, the project should allocate productive land to the affected people so that they can have productive land and generate income for their families. Also, there should be support in terms of technical training on farming, providing plant varieties with improved quality, allocation and improvement of water systems, pest control and pest control techniques, modern production equipment, etc. for them, resulting in an increase in the income from farming.